Ge2Sb2Te5-based nanocavity metasurface for enhancement of third harmonic generation. (2nd December 2021) - Li, Yang; Zhang, Xuecai; Tang, Yutao; Cai, Wenfeng; Liu, Kuan; Mao, Ningbin; Li, Kingfai; Deng, Junhong; Liu, Yanjun; Cao, Tun; Li, Guixin
Abstract: The third-order nonlinear processes in nanophotonic devices may have great potentials for developing ultra-compact nonlinear optical sources, ultrafast optical switches and modulators, etc. It is known that the performance of the nonlinear nanophotonic devices strongly relies on the optical resonances and the selection of appropriate nonlinear materials. Here, we demonstrate that the third harmonic generations (THG) can be greatly enhanced at subwavelength scale by incorporating α-Ge2 Sb2 Te5 (α-GST) into the nanocavity metasurface. Under pumping of a near-infrared femtosecond laser, the THG from the nanocavity metasurface is ∼50 times stronger than that from the bare GST planar film. In addition, the nanocavity metasurface also provides a powerful platform for characterizing the third-order nonlinear susceptibility of the active medium in the cavity. We expect that the GST-based nanocavity metasurface could open new routes for achieving high efficiency nonlinear nanophotonic devices.